Tradisi Haul Mbah Supondriyo Desa Sepande Sebagai Sumber Belajar Keberagaman Budaya Berbasis Etnopedagogi Di Sekolah Dasar - Olyssia, Olive; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2024)
Ethnopedagogy is simply culture-based learning, both used as a source of learning and as a learning medium. One culture that has high educational value is the Haul Mbah Supondriyo tradition, an annual commemoration event to honor local figures who are respected for their services in establishing Sepande Village. The purpose of this study is to explore more deeply how the Haul Mbah Supondriyo tradition can be integrated as a learning resource for elementary school students in accordance with the independent curriculum. The research method uses qualitative research with ethnographic methods. The data collection techniques used are participatory observation, in-depth interviews, and documentation studies. There are four informants who are the sources of this study including village government figures, cultural figures, community leaders who are their descendants, and youth figures. The data analysis techniques used are data reduction, data presentation, and verification. The results of this study indicate that the Haul Mbah Supondriyo tradition is a hereditary tradition of the residents of Sepande Village which has a meaning as a form of gratitude, gratitude to the founding figure, and praying to God Almighty so that Sepande Village is always safe, peaceful, and free from negative things. In addition, Haul Mbah Supondriyo contains materials related to cultural diversity contained in several contents such as Social Studies, Pancasila Education and Indonesian. The findings of the material are then integrated with learning that can be applied in elementary schools, especially phase C based on learning achievements and learning objectives. The material is developed in the form of digital and non-digital teaching materials.